Japanese and Javanese Directive Forms: A Study in Sociolinguistics - Teguh Santoso (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Abstract This paper is based on a study on directive forms in Japanese and Javanese Languages. The study combines a qualitative and sociolinguistically informed comparative method. The data were taken from different sources, namely Shin Suikodenand Jin (a Japanese novel and play respectively), Ketoprak Wiswakarman (a traditional Javanese play), and Panjebar Semangat (a Javanese magazine), and were then analyzed from a contrastive linguistic perspective. Theories on Japanese and Javanese descriptive sentences, namely those of Ishii,[1] Masuoka,[2] Poedjosoedarmo,[3] Sasangka,[4] and Wedhawati,[5] were used. In addition, Sudaryanto’s,[6] descriptive method, Sanada’s,[7] concept of Sociolinguistics, as well as Tarigan’s,[8] Ishiwata and Takahashi’s,[9] theories of contrastive linguistics were also consulted. The study aimed to describe the similarities and differences between Japanese and Javanese directive sentences based on the data from the dialogs. The study concludes that the speech levels used by the addressers and addressees in the Japanese dialogs are those of futsuugo and teineigo, which are comparable to those of ungguh-ungguh ngoko and ungguh-ungguh madya/krama in the Javanese dialogs. Keywords: directive; request; Japanese; Javanese; Sociolinguistics